2023
DOI: 10.26911/thejhpb.2023.08.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marital Status and Social Support on Antenatal Depression: A Meta-Analysis

Abstract: Background: Pregnancy is a period of increased vulnerability to depression incidence, especially if the pregnancy is accompanied by additional demands. Antenatal depression is depression that occurs during pregnancy characterized by certain symptoms, namely anxiety, distress, confusion, and excessive fear. The study aims to estimate the effect size of marital status and social support on the incidence of antenatal depression in pregnant women. Subjects and Method:The study used systematic review and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The mean depression score for the lowlevel adaptation group exceeded the threshold, indicating possible depression risk (COPE, 2017;RNAO, 2018), further highlighting the relevance of addressing and fostering adequate pregnancy adaptation as a potential preventive measure against prenatal depression. In our study, unmarried status emerged as a risk predictor, consistent with recent meta-analysis studies (Nugrahaeni et al, 2023;Yin et al, 2021), which found that unmarried expectant mothers had significantly higher odds of experiencing depression. This association may stem from negative public attitudes toward unmarried pregnancies, as pregnancies within married couples are generally more socially accepted and welcomed in Taiwan (Lai, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean depression score for the lowlevel adaptation group exceeded the threshold, indicating possible depression risk (COPE, 2017;RNAO, 2018), further highlighting the relevance of addressing and fostering adequate pregnancy adaptation as a potential preventive measure against prenatal depression. In our study, unmarried status emerged as a risk predictor, consistent with recent meta-analysis studies (Nugrahaeni et al, 2023;Yin et al, 2021), which found that unmarried expectant mothers had significantly higher odds of experiencing depression. This association may stem from negative public attitudes toward unmarried pregnancies, as pregnancies within married couples are generally more socially accepted and welcomed in Taiwan (Lai, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…In the absence of a universally accepted prevention strategy, the identification of risk factors is vital for early detection. Although certain risk factors, such as low social support, limited income, single status, young age, and a family history of depression, have been identified through meta-analytic methodologies (Nugrahaeni et al, 2023;O'Connor et al, 2019), limited research has explored its relationship with the multidimensional burden of physical symptoms during pregnancy.…”
Section: Introductionmentioning
confidence: 99%